2010
DOI: 10.1111/j.1467-7717.2010.01200.x
|View full text |Cite
|
Sign up to set email alerts
|

Crime in post‐Katrina Houston: the effects of moral panic on emergency planning

Abstract: This study used a mixed methods approach to estimate whether a moral panic occurred after Hurricane Katrina forced the evacuations of more than 250,000 people to Houston, Texas. The study viewed data from the Houston Police Department combined with a qualitative review of references of criminal activity in local print media. In total, over 8,500 lines of text were analysed to discern themes associated with media representations of the influence of evacuees on the city of Houston. There was little evidence of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Indeed, there were 73 total arrests of evacuees for Uniform Crime Reports (UCR) Part I crimes, with none for the offenses of murder/homicide or rape. 6 These findings suggest that evacuee presence did not substantially impact the crime trends in Houston, findings congruent with those of other scholars who have examined this topic (Settles & Lindsay, 2011; Verano, Schafer, Cancino, Decker, & Greene, 2010).…”
Section: Resultssupporting
confidence: 74%
“…Indeed, there were 73 total arrests of evacuees for Uniform Crime Reports (UCR) Part I crimes, with none for the offenses of murder/homicide or rape. 6 These findings suggest that evacuee presence did not substantially impact the crime trends in Houston, findings congruent with those of other scholars who have examined this topic (Settles & Lindsay, 2011; Verano, Schafer, Cancino, Decker, & Greene, 2010).…”
Section: Resultssupporting
confidence: 74%
“…In an example of disaster migration triggered by a natural disaster, after hurricanes Katrina, Rita, and Wilma hit the south-eastern coast of the US, over one million people were evacuated from metro New Orleans (Landry et al 2007). About 250,000 of these people fled to the nearby city of Houston (Settles and Lindsay 2011), meaning that overnight the Houston utilities had an extra to have received high numbers of refugees and asylum seekers in recent years; this has occurred around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The crime-rate findings presented to the Nicolet Commission are consistent with the literature on crime and disasters. Several studies have demonstrated that crime epidemics and looting are rare phenomena (Cromwell et al, 1995;Siman, 1977;Quarantelli, 2001;Zahran et al, 2009), mostly misinterpretations by both the media and members of the public (Settles and Lindsay, 2011). Even in geographical areas where disaster victims are taking shelter, research results still show that crime rates remain stable despite temporary but drastic demographic changes (Varano et al, 2009).…”
Section: Introductionmentioning
confidence: 99%